2018
DOI: 10.21276/apalm.1874
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Study of Infectious Granulomatous Skin Lesions

Abstract: Background: Granulomas are the commonest lesions that the pathologists come across in routine practice. Granulomatous inflammation is a distinctive pattern of chronic inflammation that is encountered in a number of infectious and non-infectious conditions. A definitive diagnosis made by demonstration of the etiological agent is essential, which will bear an impact on patient management and outcome.Methods: This is a retrospective study considering the cases of 2 years. The cases diagnosed as infectious granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
(6 reference statements)
2
2
0
Order By: Relevance
“…4 An identical histologic picture is produced by several causes and conversely a single cause may produce varied histologic pattern. 5 Out of the total 138 cases included in the present study age and sex distribution revealed that majority of cases belonged to the age group of 21-40 years, 68 (49.28%) cases followed by 41-60 6 Also, similar findings were reported with Permi et al and Potekar et al 7,8 A contrasting result was seen with Queiros et al who had 51-60 years as the most common age group for presentation. 9 Our study showed a male preponderance 98 (71.01%) cases, whereas by females were 40(28.99%) cases with M:E ratio of 1.9:1.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…4 An identical histologic picture is produced by several causes and conversely a single cause may produce varied histologic pattern. 5 Out of the total 138 cases included in the present study age and sex distribution revealed that majority of cases belonged to the age group of 21-40 years, 68 (49.28%) cases followed by 41-60 6 Also, similar findings were reported with Permi et al and Potekar et al 7,8 A contrasting result was seen with Queiros et al who had 51-60 years as the most common age group for presentation. 9 Our study showed a male preponderance 98 (71.01%) cases, whereas by females were 40(28.99%) cases with M:E ratio of 1.9:1.…”
Section: Discussionsupporting
confidence: 78%
“…The findings are concordant with those of Potekar et al in which lupus vulgaris constituted 2(2.98%) cases as commonest subtype. 8 The present study showed that out of total 138 cases, 26(18.84%) showed concordance between clinical and histopathological diagnosis, 98(71.01%) cases showed partial consistency and 14(10.14%) cases were discordant. Vaishali R Makwana et al showed that out of 105 cases, 69(65.7%) were concordant, 16(15.23%) cases were discordant and 20(19.04%) cases were undecided.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations